Cantilevers: Multi-Tool in Orthodontic Treatment - Malgorzata Bilinska; Kasper Dahl Kristensen; Michel Dalstra (MDPI AG, 2022)
This review aims to discuss and illustrate various uses of cantilevers to solve multiple clinical issues and prove their versatility. Cantilevers are commonly used in the segmented arch technique, and they can be designed to solve various clinical problems with highly predictable results. Its design and shape can modify the various combinations of vertical and horizontal forces. The novel trend is to combine cantilevers with skeletal anchorage. Cantilevers offer a very simple and statically determined force system. The advantage is the control over side effects, which normally occur on the anchor teeth and the occlusion. The disadvantages include possible side effects on the anchorage unit, when the anchorage is poorly controlled. The review highlights the clear benefits of cantilever use in complex corrections of single teeth, segments, and entire arch with a diminished effect on the dentition, also with the use of skeletal anchorage. With their simple and easily tailored design, these springs can be called an orthodontic multi-tool.